2017
DOI: 10.18203/2320-1770.ijrcog20173484
|View full text |Cite
|
Sign up to set email alerts
|

A study on contraceptive knowledge, attitudes and practices among women in the reproductive age group

Abstract: Background: India, with one of the world’s fastest growing populations, is a nation very much in need of contraceptive counselling. To assess the knowledge and attitude regarding family planning methods and contraceptive practices among women of reproductive age group.Methods: A cross-sectional study was performed in which 547 women in the reproductive age group i.e., 15-45 years, attending a tertiary care hospital in Mumbai were interviewed with predesigned validated questionnaire. A total of 547 women were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 2 publications
0
10
1
Order By: Relevance
“…In other studies done on the knowledge, attitude and practice of contraception majority of the participants were in the same age group. 8,9 An extensive review of literature did not reveal many studies done among pregnant women in India. Most of the studies have been done among non pregnant women in reproductive age group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other studies done on the knowledge, attitude and practice of contraception majority of the participants were in the same age group. 8,9 An extensive review of literature did not reveal many studies done among pregnant women in India. Most of the studies have been done among non pregnant women in reproductive age group.…”
Section: Resultsmentioning
confidence: 99%
“…This was found to be lower than the awareness rate found in other Indian studies of 91%, 82.8% and 100%. 2,9,10 Out of the primigravidae 44.6% and of the multigravidae 19.1% were not aware that contraceptives are available free of cost in the Government hospitals and health centres. As expected, the awareness was found to be significantly greater among multigravidae when compared to primigravidae.…”
Section: Resultsmentioning
confidence: 99%
“…11 Contrary to this, Shukla and researchers in their research study reported social circle as main source of information regarding family planning methods. 12 As far as the utilization of various family planning methods is concerned, nearly 1/3 rd of the study subjects were using one or other type of contraceptive method. Sterilization was the most common method and lactational amenorrhea was the least used method.…”
Section: Discussionmentioning
confidence: 99%
“…Women education and counseling can play an important role to adopt family planning methods. The mothers should be given information about contraceptives at every visit to the health services to motivate them [7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%